S. E. Lehmberg, The Later Parliaments of Henry VIII, 1536-1547 - Wąsowicz, Marek (Czasopismo Prawno-Historyczne, 1978)
Recenzja: S. E. Lehmberg, The Later Parliaments of Henry VIII, 1536-1547, Cambridge University Press 1977, ss. 379.